Measuring the Deflection of the Vertical via Local Reference Point Surveying and Pointing Calibration of a VLBI Telescope: A Case Study at the Urumqi Station. Issue 10 (12th October 2021) - Zhang, Zhibin; Ma, Xiaohui; Sun, Zhongmiao; Zhang, Ali; Yuan, Ye; Sun, Zhengxiong
Abstract: According to Newton's law of universal gravitation, the movement of matter and the change in density cause a gravitational variation. Due to the anisotropic distribution of matter, the vertical and the normal directions at a point on the ground are probably inconsistent, which is referred to as the deflection of the vertical (DOV) and is indispensable to astrogeodetic and geophysics research. Two new non‐optical methods, including small network transformation and azimuth‐axis inclination inversion, are proposed to determine the DOV at a very long baseline interferometry (VLBI) telescope at the Urumqi station. A generalized expression of the pointing calibration model considering axis‐related errors is also presented. Therefore, the pointing calibration model and indirect model used for reference point (RP) determination are unified by redefining their coordinate system, angle direction, and axis‐related errors. The DOV given by the small network transformation agrees well with the DOVs determined by the real surveying and other different models. Due to the possible asymmetric coverage of calibrating sources in the north‐south direction in antenna pointing calibration, the north‐south DOV component based on azimuth‐axis inclination inversion differs from the surveyed value. However, the west‐east DOV component fits well in both direction and magnitude. The proposed methods enable the VLBI telescope to sense the direction of the local plumb line by introducing local leveling. We also establish the connections among VLBI delay observation, RP determination, and telescope pointing calibration, which has a benefit to multi‐tech systematic error identification, monitoring, and correction. The research indicates that telescope point calibration can also be taken as a regular technique to monitor systematic error. Key Points: Two new non‐optical methods are proposed to determine the deflection of the vertical at a very long baseline interferometry (VLBI) telescope A generalized expression of a pointing calibration model considering axis‐related errors is given The connection among VLBI delay observation, reference point determination and telescope pointing calibration is established